Studi Etnografi Dalam Kerangka Masyarakat Dan Budaya - Kamarusdiana Kamarusdiana (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
AbstractCommunities with all their cultures have quite strong sociological roots. Culture that results from social interaction makes a distinctive value in that society. The forerunner of culture is an important aspect in the social framework. Research on this aspect of culture uses ethnographic studies. In its implementation ethnography emphasizes the existing aspects of culture. This is an important feature of ethnographic studies. As ethnographic qualitative research conducts in-depth analysis of the culture under study. On the other hand, there is a fairly close link between ethnography and society and culture as a result of their creativity. Therefore, this linkage needs to be applied positively, where it is necessary to use ethnographic studies as an alternative form of conducting research on culture in the community.Keywords: Ethnography, Culture, Society AbstrakMasyarakat dengan segala kebudayaannya memiliki akar sosiologis yang cukup mengakar kuat. Kebudayaan yang dihasilkan dari interaksi sosial menjadikan nilai distingsi tersendiri dalam masyarakat tersebut. Cikal bakal kebudayaan merupakan aspek penting dalam kerangka sosial kemasyarakatan. Penelitian akan aspek kebudayaan ini menggunakan studi etnografi. Dalam implementasinya etnografi menekankan pada aspek kebudayaan yang ada. Hal inilah menjadi ciri penting dari studi etnografi. Sebagai penelitian kualitatif etnografi melakukan analisa secara mendalam terhadap kebudayaan yang diteliti. Disisi lain, terdapat keterkaitan yang cukup erat antara etnografi dengan masyarakat dan kebudayaan sebagai hasil kreatifitasnya. Oleh sebab itu, keterkaitan tersebut perlu diaplikasikan secara positif, di mana perlunya menggunakan studi etnografi sebagai bentuk alternatif dalam melaksanakan penelitian tentang kebudayaan di masyarakat. Kata Kunci: Etnografi, Kebudayaan, Masyarakat